Environmental Education Awareness among School Teachers in Relation to Level and Residential Background - Mary, Susheela; Thomas, Tarence (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The present study has been conducted on a stratified sample of 120 school teachers to study their environmental awareness and participation in respect to their level and residential background. A self-made questionnaire was used to collect data, which was treated with suitable statistical technique‘t’ tests. The results significant variations in the environmental awareness and participation of secondary and elementary school teachers with the former scoring higher. Significant difference was also noted in the environmental awareness of urban and rural school teachers with urban teachers scoring higher However, interaction effects of both variables (level and residential background) showed insignificant differences upon environmental education awareness.